Rise & Shine Together: Leadership Training to Build Innovative and Collaborative Organizations - Edoardo Tondang; Pralayar Fanny Fadesthi; Muhammad Dika Randi Rawindra; Muhammad Zahwan; Irma Eliyani; Nikita Zahra; Icha Machdita Risma Apriani; Najwa Indira Fitri; Millatus Salamah (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2025)
The "Rise & Shine Together" training aims to improve the leadership skills of members of the Family Law Study Center (PUSAKA) of Sultan Aji Muhammad Idris Samarinda State Islamic University. The problems faced by partner organizations include low initiative, communication, and collaboration between members. The method used was Participatory Experiential Leadership Training (PELT) through interactive seminars, roleplay, and case studies involving 18 participants. Cognitive evaluation was conducted by comparing pre-test and post-test results, showing an average increase in understanding of 8.76%. Participants' activeness, understanding and attention reached more than 80%. This training is effective in creating a learning environment that supports the development of leadership skills and is expected to be applied in organizations to achieve their vision and mission. Pelatihan "Rise & Shine Together" bertujuan untuk meningkatkan keterampilan kepemimpinan di antara anggota Pusat Studi Hukum Keluarga (PUSAKA) di Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda. Organisasi mitra menghadapi tantangan seperti rendahnya inisiatif, komunikasi, dan kolaborasi di antara anggota. Metode Participatory Experiential Leadership Training (PELT) diimplementasikan melalui seminar interaktif, permainan peran, dan studi kasus yang melibatkan 18 peserta. Evaluasi kognitif yang membandingkan hasil pra-tes dan pasca-tes menunjukkan peningkatan pemahaman rata-rata sebesar 8,76%. Keaktifan, pemahaman, dan keterlibatan peserta melebihi 80%. Pelatihan ini secara efektif menumbuhkan lingkungan belajar yang kondusif untuk pengembangan keterampilan kepemimpinan, diharapkan dapat diterapkan dalam organisasi untuk mencapai visi dan misinya.